Biotic Resistance and Fluctuating Resources: Key Factors for Invasion Success? - Pathak, Hom N (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
To explain the process of biological invasion, several hypotheses have been put forward e.g. enemy release hypothesis, invasional meltdown hypothesis, novel weapon hypothesis, fluctuation resources hypothesis, biotic resistant hypothesis, etc. I collected the abstracts from search engines on the internet. I searched for biotic resistance and fluctuation resources hypotheses, collected 25 research papers, and reviewed them. Out of nine studies written for the biotic resistance hypothesis, five were in support and the other five were against the hypothesis. However, there seems only evidence against the fluctuation resources hypothesis. For it, I found four articles in support of this hypothesis. Any hypothesis alone cannot explain the causes behind the invasion's success. Therefore, I have an opinion to establish a combined theory for it.